Development of marine observation system using LPWA communication system for marine IoT service - Se-Hoon Kim; Min-Ho Jeon; Yeon-Ju Jo; Chang-Heon Oh (Institute of Advanced Engineering and Science, 2020)
Because oceans account for 70.8% of the Earth's surface, various internet of things (IoT) applications for the marine industry are being researched and developed. The success of an IoT technology in the maritime industry depends on the location tracking technology used and how far it can communicate. In this study, we implemented a marine observation system using low power wide area (LPWA) communication technology to provide maritime IoT services. The proposed marine observation system consists of a marine IoT module and an ocean observation monitoring system. The information collected is GPS information and communication signal reception strength. As a result of an actual field test, we were able to obtain the distance to the gateway by measuring the position through the marine IoT module, and we found that the intensity of communication was proportional to the change in sea level.